(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This thesis delves into fresh approaches to managing personnel in the banking sector, with the goal of boosting organizational efficiency, output, and employee contentment. In an age defined by swift technological progress, shifting customer demands, and fierce competition, banks are under pressure to optimize their workforce effectively. Conventional personnel management methods often prove inadequate in tackling the ever-changing demands of the contemporary banking environment. This study explores inventive techniques and tactics that have the potential to transform personnel management practices within banks, ultimately driving improved performance and sustainable expansion.